Local Fractional Laplace Variational Iteration Method for Solving Linear Partial Differential Equations with Local Fractional Derivative - Ai-Min Yang; Jie Li; H. M. Srivastava; Gong-Nan Xie; Xiao-Jun Yang (Discrete Dynamics in Nature and Society)
The local fractional Laplace variational iteration method was applied to solve the linear local fractional partial differential equations. The local fractional Laplace variational iteration method is coupled by the local fractional variational iteration method and Laplace transform. The nondifferentiable approximate solutions are obtained and their graphs are also shown.